Transformasi Tradisi Sadranan dalam Integrasi Nilai Islam dan Budaya Jawa - Rahmawati, Indah (Postgraduate Studies UIN Sunan Ampel Surabaya, 2025)
This study aims to examine the implementation and transformation of the Sadranan tradition as an effort to preserve Javanese cultural heritage in the contemporary era. The tradition faces challenges due to lifestyle changes, population mobility, and the influence of global culture, which reduce young people’s attention to traditional values. This research employs a qualitative descriptive approach using literature study methods, analyzed through the perspectives of cultural anthropology and cultural functionalism theory. The findings reveal that the Sadranan tradition has undergone symbolic and procedural simplifications, such as shorter rituals, translated prayers into Indonesian, and reduced offerings, while maintaining its spiritual and social essence. These adaptations demonstrate the ability of Javanese society to sustain communal solidarity, ancestral reverence, and Islamic spirituality through cultural transformation. The novelty of this study lies in interpreting Sadranan as a dynamic form of local cultural adaptation that preserves both spiritual and social continuity amid modernization.